Diamine monomer, polyimide compound, preparation method and application

By introducing trifluoromethyl, ester and amide groups into polyimide materials and optimizing the molecular chain structure, the problems of high transparency and thermal expansion coefficient of traditional polyimide are solved, and a colorless, transparent, low-CTE polyimide film is prepared, which is suitable for flexible display devices.

CN120647551APending Publication Date: 2025-09-16HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510701369.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Traditional polyimide materials have poor transparency, low light transmittance, and high thermal expansion coefficient, and cannot take into account both thermal and optical properties, which limits their application in high-end fields.

Method used

Diamine monomers containing trifluoromethyl, ester and amide groups are introduced to prepare polyimide compounds through condensation reaction, and the molecular chain structure is optimized to improve transparency and reduce the thermal expansion coefficient while maintaining mechanical properties.

Benefits of technology

A colorless and transparent polyimide film with a low thermal expansion coefficient has been achieved, which improves the high definition and dimensional stability of display devices and is suitable for precision optical devices such as flexible display substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120647551A_ABST
    Figure CN120647551A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic flexible display equipment materials, and particularly discloses a diamine monomer, a polyimide compound, a preparation method and application. According to the invention, trifluoromethyl with strong electronegativity is introduced into the structure of a diamine monomer, the electron donating ability of the diamine monomer is reduced, the CTC effect in / between molecular chains is weakened, the optical transparency of the polyimide film is improved, in order to avoid excessive sacrifice of thermal and mechanical properties, trifluoromethyl is introduced, and meanwhile, groups containing amido bonds and ester bonds are also introduced, so that the polyimide film is prepared. Through the synergistic effect of trifluoromethyl, ester group and amide group, while the optical performance is improved, the loss of thermal stability and mechanical performance of the material is avoided, the technical problem that the thermal performance and the optical performance cannot be considered at the same time is solved, and the polyimide film material has a wide application prospect in the field of polyimide film material preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic flexible display device materials, and in particular to a diamine monomer, a polyimide compound, a preparation method and an application thereof. Background Art

[0002] Polyimide (PI), a high-performance polymer, is widely used in aerospace, microelectronics, optoelectronic displays, and other fields due to its excellent thermal stability, mechanical properties, chemical stability, and dielectric properties. With the rapid development of flexible display technology, various display devices are beginning to use organic flexible substrates instead of fragile inorganic glass substrates. Due to its excellent comprehensive properties, polyimide has become a key material in the manufacture of flexible display substrates and other optical devices.

[0003] Traditional polyimides are generally synthesized using dianhydrides and diamines as the main raw materials through a step-by-step polymerization reaction. Common dianhydrides such as pyromellitic dianhydride (PMDA) and 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), and diamines such as 4,4'-diaminodiphenyl ether (ODA), have numerous rigid groups in their molecular structures, resulting in strong interactions between the molecular chains. This easily leads to dense stacking during polymerization, resulting in a high degree of conjugation of the polymer molecular chains. This results in polyimide films generally appearing brown or tan in color and having poor transmittance in the visible light region, significantly limiting their application in fields such as optical displays.

[0004] At the same time, in the field of microelectronics packaging, the continuous increase in chip integration and the continued reduction in device size have placed stringent requirements on the coefficient of thermal expansion (CTE) of polyimide materials. Because polyimide molecular chains made from traditional raw materials lack flexibility and have a high thermal expansion coefficient, the high CTE can induce thermal stress when the temperature changes, increasing the risk of interface failure, thereby reducing the reliability and service life of the device. Therefore, the development of transparent polyimide materials with both high CTE and high transmittance is of great significance to promoting the widespread application of polyimide materials in high-end fields. Summary of the Invention

[0005] In order to solve the technical problems of poor transparency, low light transmittance and inability to balance thermal and optical properties of current polyimide materials, the present invention provides a diamine monomer, a polyimide compound, a preparation method and an application thereof.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0007] In a first aspect, the present invention provides a diamine monomer, the structure of which is shown in formula (I):

[0008]

[0009] Compared with the prior art, the present invention introduces a strongly electronegative trifluoromethyl group into the structure of the diamine monomer, reduces the electron-donating ability of the diamine monomer, weakens the CTC effect within / between the molecular chains, and improves the optical transparency of the polyimide film. Further, when improving the optical properties, in order to avoid excessive sacrifice of thermal and mechanical properties, while introducing the trifluoromethyl group, a group containing an amide bond and an ester bond is also introduced; wherein, the amide group can form an intermolecular hydrogen bond, so that the interaction between the molecular chains is enhanced, and the mechanical properties such as tensile strength and modulus of the polyimide film are improved, while also helping to maintain the structural stability of the polyimide molecule, thereby improving the chemical stability and thermal stability of the material as a whole; the introduction of the ester group is conducive to improving the solubility of the polyimide in organic solvents, and at the same time, synergistically with the amide group, it is conducive to improving the thermal stability of the polyimide. Through the synergistic effect of the trifluoromethyl group, the ester group and the amide group, while improving the optical properties, the loss of the thermal stability and mechanical properties of the material is also avoided, solving the technical problem that thermal performance and optical performance cannot be taken into account at the same time, and has broad application prospects in the field of preparing polyimide film materials.

[0010] In a second aspect, the present invention further provides a method for preparing a diamine monomer, comprising the following steps:

[0011] Step a: In the presence of a first catalyst and solvent a, aniline and hexafluoroacetone undergo electrophilic substitution reaction to obtain intermediate 1 represented by formula (I-a);

[0012]

[0013] Step b, in the presence of a second catalyst, an acid-binding agent, and solvent b, intermediate 1 undergoes an acylation reaction with p-nitrobenzoyl chloride to obtain intermediate 2 represented by formula (I-b);

[0014]

[0015] In step c, intermediate 2 is subjected to hydrogenation reduction reaction in the presence of the third catalyst and solvent c to obtain the diamine monomer represented by formula (I). The specific reaction route is as follows:

[0016]

[0017] The synthesis method of the diamine monomer provided by the present invention has a wide range of raw material sources, a simple reaction route, and is easy to implement industrial-scale production and application.

[0018] Furthermore, in step a, the molar ratio of aniline to hexafluoroacetone is 1:(1-3).

[0019] Furthermore, in step a, the first catalyst comprises one or both of p-toluenesulfonic acid and trifluoromethanesulfonic acid.

[0020] Furthermore, in step a, the molar ratio of the aniline to the first catalyst is 1:(0.03-0.05).

[0021] Furthermore, in step a, the solvent a is xylene.

[0022] Furthermore, in step a, the ratio of the solvent a to aniline is (2-5) mL:1 g.

[0023] Furthermore, in step a, the temperature of the electrophilic substitution reaction is 100° C. to 130° C., and the reaction time is 15 h to 20 h.

[0024] Furthermore, in step b, the molar ratio of the intermediate 1 to p-nitrobenzoyl chloride is 1:(2-4).

[0025] Furthermore, in step b, the second catalyst includes at least one of 4-dimethylaminopyridine, pyridine or triethylamine.

[0026] Furthermore, in step b, the molar ratio of the second catalyst to the intermediate 1 is (0.3-0.5):1.

[0027] Furthermore, in step b, the solvent b is tetrahydrofuran, and the acid binding agent is triethylamine.

[0028] Furthermore, in step b, the temperature of the acylation reaction is -5°C to 25°C, and the reaction time is 0.5h to 1h.

[0029] Furthermore, in step c, the third catalyst includes one or both of palladium carbon and Raney nickel.

[0030] Furthermore, in step c, the mass ratio of the intermediate 2 to the third catalyst is (6-7):1.

[0031] Furthermore, in step c, the solvent c is anhydrous ethanol.

[0032] Furthermore, in step c, the temperature of the hydrogenation reduction reaction is 30° C. to 60° C., the pressure is 3 MPa to 4 MPa, and the reaction time is 8 h to 10 h.

[0033] The above-mentioned preferred reaction conditions are conducive to improving the yield and purity of the prepared diamine monomer, laying the foundation for the subsequent synthesis of polyimide film.

[0034] In a third aspect, the present invention further provides a polyimide compound, the structure of which is shown in formula (II):

[0035]

[0036] In the formula Select one of the following structures:

[0037]

[0038] Wherein, m and n are positive integers, and m+n=10, m=2-10.

[0039] Relative to the prior art, the polyimide compound structure provided by the present invention introduces trifluoromethyl, ester group and amide group, trifluoromethyl can weaken the electron-donating ability of the molecule, weaken the CTC effect, and by accurately regulating the amount and position of the introduction of trifluoromethyl, it can more effectively reduce the light absorption of electronic transitions and improve optical transparency; At the same time, the trifluoromethyl group has a large electronegativity, which can optimize the molecular chain arrangement of the polyimide, making it more regular and orderly, reducing the thermal motion space, and reducing the thermal expansion coefficient; The hydrogen bond formed by the amide bond can strengthen the intermolecular force, while improving the resistance to thermal deformation and reducing the degree of thermal expansion, it is also conducive to improving the mechanical properties of the polyimide; The ester group has a low polarity and can destroy the rigid structure and intermolecular hydrogen bond of the polyimide main chain, reducing interchain stacking, thereby helping to improve the solubility and flexibility of the polyimide. The various functional groups in the polyimide compound of the present invention work synergistically, while improving the optical properties of the material and reducing the thermal expansion coefficient, it can also effectively maintain the mechanical properties of the material, achieve the optimized balance of the comprehensive performance of the material, and have good application prospects in the fields of flexible display and the like, and have high practical value.

[0040] In a fourth aspect, the present invention further provides a method for preparing the above-mentioned polyimide compound, comprising the following steps:

[0041] The diamine monomer and the dianhydride monomer are subjected to a condensation reaction, followed by a dehydration cyclization reaction to obtain a polyimide compound represented by formula (II);

[0042] Wherein, the diamine monomer is a diamine monomer represented by formula (I) or a mixed monomer of a diamine monomer represented by formula (I) and 2,2'-bis(trifluoromethyl)diaminobiphenyl;

[0043]

[0044] The dianhydride monomer is 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, 4,4'-oxydiphthalic anhydride or 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride.

[0045] Compared with the prior art, the present invention adopts a chemical imidization reaction for polymerization, which is beneficial to improving the optical properties of the film, reduces the temperature of the reaction system, thereby avoiding color changes caused by segment oxidation at high temperatures, and can reduce or even avoid side reactions caused by high temperatures, thereby improving the quality of the prepared polyimide compound.

[0046] Furthermore, the preparation method of the polyimide compound specifically comprises the following steps:

[0047] S1, under an inert atmosphere, dissolving a diamine monomer and a dianhydride monomer in a polar aprotic solvent, and reacting at -5°C to 25°C for 12 hours to 24 hours to obtain a polyamic acid reaction solution;

[0048] S2, adding a catalyst and a dehydrating agent to the polyamic acid reaction solution, reacting at -5°C to 25°C for 12 hours to 24 hours, washing, and drying to obtain a polyimide compound represented by formula (II). The specific synthesis route is as follows:

[0049]

[0050] The preparation method of the polyimide compound provided by the present invention has low production cost, short synthesis steps, simple operation, mild reaction conditions, high purity of the prepared product, good industrial utilization value, and high promotion and application value.

[0051] Furthermore, in step S1, the polar aprotic solvent includes at least one of N,N-dimethylacetamide, N,N-dimethylformamide or N-methylpyrrolidone.

[0052] Furthermore, in step S1, the molar ratio of the diamine monomer represented by formula (I) to 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl is (0.2-1):(0.8-0).

[0053] Furthermore, in step S1, the molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.2).

[0054] Furthermore, in step S1, the solid content of the polar aprotic solvent is controlled to be 10% to 30%.

[0055] It should be noted that the inert atmosphere in the present invention can be provided by conventional inert gases in the art, such as nitrogen, argon, etc.

[0056] Furthermore, in step S2, the molar ratio of the catalyst, the dehydrating agent and the diamine monomer is (1-5):(5-10):1.

[0057] Furthermore, in step S2, the catalyst is at least one of pyridine, collidine or quinoline.

[0058] Furthermore, in step S2, the dehydrating agent is acetic anhydride.

[0059] It should be noted that after the reaction in step S2 is completed, a post-processing process is also included: adding a poor solvent to the reaction solution for precipitation, solid-liquid separation, and drying to obtain a polyimide compound.

[0060] Furthermore, the poor solvent is methanol, anhydrous ethanol or deionized water.

[0061] In a fifth aspect, the present invention further provides a low CTE colorless and transparent polyimide film, comprising the above-mentioned polyimide compound or a polyimide compound prepared by any of the above-mentioned preparation methods.

[0062] The polyimide compound of the present invention incorporates trifluoromethyl, ester, and amide groups. The trifluoromethyl group loosens the molecular chains of the polyimide, effectively inhibiting the formation of CTCs within the polyimide molecules. Furthermore, the amide and ester groups enhance optical properties while avoiding adverse effects on thermal and mechanical properties. Furthermore, the introduction of a 2,2'-bis(trifluoromethyl)-4,4'-diaminobenzenediamine monomer, by regulating its ratio with the diamine monomer represented by formula (I), further enhances the overall performance of the polyimide.

[0063] In a sixth aspect, the present invention further provides a method for preparing the above-mentioned low CTE colorless and transparent polyimide film, comprising the following steps:

[0064] The polyimide compound is dissolved in an organic solvent, casted, the solvent is evaporated, and the film is peeled off to obtain a low CTE colorless and transparent polyimide film.

[0065] Furthermore, the organic solvent is dimethylacetamide, and the solid content is controlled to be 8% to 10%.

[0066] Furthermore, the temperature for film laying is 60° C. to 80° C., and the time for evaporating the solvent after film laying is 6 h to 8 h.

[0067] In a seventh aspect, the present invention further provides a flexible display device material, comprising the above-mentioned low CTE colorless and transparent polyimide film.

[0068] The polyimide film provided by the present invention is colorless and transparent, which helps ensure high-definition and color reproduction of displayed images. It also has the advantage of a low thermal expansion coefficient. Even with significant temperature fluctuations, the polyimide film maintains high dimensional stability and does not undergo significant deformation due to thermal expansion and contraction. This is crucial for the manufacture of precision optical devices such as flexible display substrates. In flexible display technology, the dimensional stability of the substrate directly affects the performance and service life of the display device. This polyimide film provides solid material support for the development of flexible display technology and has high application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 is the H NMR spectrum of the FBA-1 compound prepared in Example 1 of the present invention;

[0070] Figure 2 is the NMR carbon spectrum of the FBA-1 compound prepared in Example 1 of the present invention;

[0071] Figure 3 This is the nuclear magnetic hydrogen spectrum of the FBA-2 compound prepared in Example 1 of the present invention

[0072] Figure 4 This is the NMR carbon spectrum of the FBA-2 compound prepared in Example 1 of the present invention;

[0073] Figure 5 is the H NMR spectrum of the FBA compound prepared in Example 1 of the present invention;

[0074] Figure 6 is the NMR carbon spectrum of the FBA compound prepared in Example 1 of the present invention;

[0075] Figure 7 is the mass spectrum of the FBA compound prepared in Example 1 of the present invention;

[0076] Figure 8 The following are images of polyimide films PIA-1 to PIA-5 prepared in Examples 2 to 5 of the present invention; from left to right, they are PIA-1, PIA-2, PIA-3, PIA-4, and PIA-5;

[0077] Figure 9 The following are pictures of polyimide films PIA-6 to PIA-10 prepared in Examples 7 to 11 of the present invention; from left to right they are PIA-6, PIA-7, PIA-8, PIA-9, and PIA-10;

[0078] Figure 10 Graph showing the relationship between light transmittance and wavelength of polyimide films PIA-1 to PIA-10 prepared in Examples 2 to 11 of the present invention;

[0079] Figure 11 1 is an infrared spectrum of polyimide films PIA-1 to PIA-5 prepared in Examples 2 to 5 of the present invention;

[0080] Figure 12 3 are infrared spectra of polyimide films PIA-6 to PIA-10 prepared in Examples 7 to 11 of the present invention. DETAILED DESCRIPTION

[0081] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0082] In order to better illustrate the present invention, further examples are given below.

[0083] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; unless otherwise specified, the reagents used are all commercially available products or prepared by conventional methods in the art.

[0084] The compounds corresponding to the abbreviations in the following examples are: 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB), 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA), 4,4'-oxydiphthalic anhydride (ODPA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), cyclobutanetetracarboxylic dianhydride (CBDA), and 1,2,4,5-cyclohexanetetracarboxylic dianhydride (HPMDA).

[0085] Example 1

[0086] This embodiment provides a method for preparing a diamine monomer FBA:

[0087] (1) Synthesis of 2-(4-aminophenyl)-1,1,3,3-hexafluoropropan-2-ol (FBA-1)

[0088] To a 250mL single-necked flask equipped with a magnetic element, 20g (215mmol) of aniline was added, 70mL of xylene was added as a solvent, and the mixture was fixed on a heat-collecting stirrer and stirred. 36mL (288mmol) of hexafluoroacetone trihydrate was gradually added dropwise to the reaction solution. The addition was completed within 20min. 1.6g (9.3mmol) of p-toluenesulfonic acid was added as a catalyst. The oil bath was heated to 130°C and refluxed. The reaction was monitored by TLC. The reaction was complete after 16h. After the reaction solution cooled to room temperature, it was placed in a -5°C ice bath environment and crystallized for 1h. The product was completely precipitated and filtered. The filter cake was beaten with 500mL of 5% potassium carbonate solution to remove residual p-toluenesulfonic acid. After filtration, it was washed twice with 500mL of water, filtered again, and dried under vacuum at 55°C for 8h to obtain 17g of a white solid with a yield of 31%, which was recorded as FBA-1. The synthetic route is as follows:

[0089]

[0090] 1 H NMR (500MHz, DMSO-d6) δ8.19 (s, 1H), 7.30 (d, J = 8.4Hz, 2H), 6.65–6.60 (m, 2H), 5.45 (s, 2H).

[0091] 13C NMR (126MHz, DMSO-d6) δ150.57,128.01,127.17,124.88,122.58,120.29,117.17,113.69,77.41,77.18,76.95.

[0092] (2) Synthesis of 1,1,1,3,3,3-hexafluoro-2-(4-(4-nitrobenzamido)phenyl)propan-2-yl-4-nitrobenzoate (FBA-2)

[0093] To a 250mL single-necked flask equipped with a magnetic ion, 80g (479mmol) of p-nitrobenzoic acid and 70mL of thionyl chloride were added. The flask was fixed on a heat-collecting stirrer and stirred. 0.5mL of N,N-dimethylformamide was added dropwise as a catalyst. The flask was heated to 80°C in an oil bath and refluxed. The reaction was monitored by TLC. The reaction was complete in 8.5 hours. After the reaction solution cooled, it was added to a distillation apparatus and gradually heated to 120°C for atmospheric distillation at a rate of 10°C / 30min until no more fractions were distilled. After the remaining material was cooled to room temperature, it was gradually heated to 80°C for vacuum distillation at a rate of 10°C / 30min until no more fractions were distilled. The product was dried to obtain 85g of p-nitrobenzoyl chloride in a yield of 97%. The synthetic route is as follows:

[0094]

[0095] Under ice bath conditions, 8.00 g (30.9 mmol) of the above-prepared FBA-1 and 40 mL of tetrahydrofuran were added to a 250 mL single-necked flask equipped with a magnetic rod. The mixture was fixed on a normal temperature stirrer and stirred until it was completely dissolved. 9.36 g (92.5 mmol) of triethylamine was added as an acid binding agent, 1.50 g (12.3 mmol) of 4-dimethylaminopyridine was added as a catalyst, 14.30 g (77.3 mmol) of p-nitrobenzoyl chloride was dissolved in 20 mL of tetrahydrofuran and slowly added dropwise to the reaction solution. The addition was completed in 20 min, the ice water bath was removed, and the reaction was continued at room temperature. The reaction was monitored by TLC and the reaction was complete in 40 min. The reaction solution was filtered, and the filter cake was a salt byproduct. The filtrate was dropped into water to precipitate a light yellow solid. After filtration, it was purified by beating with 500 mL of water, 250 mL of 10% potassium carbonate aqueous solution, 250 mL of 10% dilute hydrochloric acid solution, 500 mL of water, and finally 60 mL of methanol. After filtration, an off-white solid was obtained, which was vacuum-dried at 55°C to obtain 14.62 g of a dinitro compound with a yield of 85%, which was recorded as FBA-2. The synthetic route is as follows:

[0096]

[0097] 1 H NMR(500MHz,DMSO-d6)δ10.86(s,1H),8.51–8.44(m,2H),8.45–8.37(m,2H),8 .37–8.30(m,2H),8.24–8.17(m,2H),8.02–7.95(m,2H),7.61(d,J=8.5Hz,2H).

[0098] 13 C NMR(126MHz,DMSO-d6)δ164.86,160.66,151.72,149.82,141.43,140.69,132.96,132.10,130 .95,130.76,129.85,127.80,124.92,124.09,123.86,123.19,120.99,120.91,120.70,83.89.

[0099] (3) Synthesis of 2-(4-(4-aminobenzamido)phenyl)-1,1,3,3-hexafluoropropane-2-yl 4-aminobenzoate (FBA)

[0100] In a 500 mL hydrogenation reactor with mechanical stirring, 6.5 g (9.87 mmol) of the prepared FBA-2 was added, 200 mL of anhydrous ethanol was added as a solvent, and 1 g of 5% palladium carbon was added as a catalyst. The lid of the reactor was tightened, nitrogen was introduced to replace the air in the reactor, and a leak test was performed to ensure that the reactor was well sealed. After the nitrogen was replaced by hydrogen, 3.5 MPa of hydrogen was introduced into the reactor. The speed was set to 240 r / min, stirring was started, and the reactor was heated at 55°C in an oil bath with a heat-collecting stirrer. The hydrogen pressure was observed by the digital display until the pressure in the reactor no longer changed, and the reaction was stopped. After the temperature in the autoclave dropped to room temperature, the pressure was released and the autoclave was opened. The reaction solution was filtered to remove palladium carbon, and the palladium carbon was quenched with water and recovered. 0.5g of alkaline activated carbon was added to the reaction solution for decolorization and then filtered. The filtrate was then dried using a rotary evaporator. Finally, the product was recrystallized using ethyl acetate / petroleum ether = 1 / 5 (v / v). After the solid precipitated, it was filtered and dried in vacuo at 55°C to obtain 3.8g of a white solid with a yield of 78%, which was recorded as FBA. Its melting point was measured to be 124-126°C. The synthetic route is as follows:

[0101]

[0102] 1H NMR(500MHz,DMSO-d6)δ10.03(s,1H),7.93–7.88(m,2H),7.76–7.72(m,4H),7.38(d,J=8.5 Hz,2H),6.71–6.65(m,2H),6.65–6.59(m,2H),6.40(d,J=4.9Hz,2H),5.82(d,J=7.4Hz,2H).

[0103] 13 C NMR (126MHz, DMSO-d6) δ170.83,166.06,161.80,155.65,152.94,142.11,132.66,130.05, 127.26,125.93,123.64,121.34,121.07,121.02,120.41,113.50,113.04,112.97,82.76.

[0104] HRMS[M+H] + (C 23 H 17 F6N3O3): Theoretical calculation value M = 498.1174, measured value M = 498.1241.

[0105] Examples 2-6

[0106] A method for preparing a low CTE colorless and transparent polyimide:

[0107] A 100 mL three-necked flask was installed on a stirring device with mechanical stirring, and an argon flow was used to replace the air in the flask, and the argon environment was always maintained. The flask was thoroughly dried using a 300 ° C hot air gun. 1.038 g (3.2430 mmol) of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB) was added to the three-necked flask under ice bath conditions, and 10.0 mL of dimethylacetamide was added. The speed was set to 200 r / min and stirred continuously until it was completely dissolved. The diamine monomer FBA prepared in Example 1 was weighed. 0.4028 g (0.8103 mmol) of 6FDA was added to a three-necked flask, and 1.5 mL of dimethylacetamide was added. After the solid was completely dissolved, 1.8000 g (4.0540 mmol) of 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6FDA) was weighed and added to the three-necked flask. 1.5 mL of dimethylacetamide was added to dissolve it. The solid content of the reaction system was controlled at 25%. After 2 h, the ice-water bath was removed. The viscosity change of the reaction solution was monitored every two hours. After stirring at room temperature for 24 h, 3.8 mL (40.54 mmol) of acetic anhydride was added to the three-necked flask as a dehydrating agent, and 0.33 mL (4.0540 mmol) of pyridine was added as a catalyst. Stirring was continued at room temperature for 24 h before terminating the reaction. The reaction solution was poured into 150 mL of methanol to precipitate a white fibrous precipitate. The product was washed twice with water and once with methanol, filtered, and dried in a vacuum at 80°C to obtain 3.18 g of a white solid with a yield of 98%, recorded as 20% FBA / 80% TFMB / 6FDA.

[0108] While the total molar amount of the diamine monomer remains unchanged, the ratio of the diamine monomers FBA and TFMB is varied, and the same method is used to prepare 40% FBA / 60% TFMB / 6FDA, 60% FBA / 40% TFMB / 6FDA, 80% FBA / 20% TFMB / 6FDA, and FBA / 6FDA, respectively. The synthetic routes are as follows:

[0109]

[0110] In the above formula, the ratio of m to n is the ratio of the diamine monomers FBA and TFMB.

[0111] Weigh 0.35 g of each of the five polymers prepared above and put them into a 15 mL centrifuge tube. Dissolve them completely with 4.0 mL of anhydrous DMAc, control the solid content to 8.75%, and centrifuge at 4000 r / min for 3 minutes. After the centrifugation is completed, use a dropper to absorb the supernatant and evenly coat it on a glass plate using a casting method. Place the glass plate on a constant temperature heating table, set the temperature to 80°C, and heat for 5 hours. After the temperature drops to room temperature, carefully peel off the film. The five films obtained were named PIA-1 (20% FBG / 80% TFMB / 6FDA), PIA-2 (40% FBG / 60% TFMB / 6FDA), PIA-3 (60% FBG / 40% TFMB / 6FDA), PIA-4 (80% FBG1 / 20% TFMB / 6FDA), and PIA-5 (FBG / 6FDA). The pictures of the obtained films are shown in the figure below. Figure 8 shown.

[0112] Examples 7-11

[0113] A method for preparing a low CTE colorless and transparent polyimide:

[0114] A 100 mL three-necked flask was placed on a stirring device with mechanical stirring, and the air in the flask was replaced with an argon flow, and the argon atmosphere was maintained. The flask was thoroughly dried using a 300°C hot air gun. 1.4867 g (4.6449 mmol) of 2,2'-bis(trifluoromethyl)diaminobiphenyl (TFMB) was placed in the three-necked flask under ice bath conditions, and 10.0 mL of dimethylacetamide was added. The speed was set to 200 r / min and stirred continuously until completely dissolved. The diamine monomer FBA prepared in Example 1 was weighed. 0.5773 g (1.1612 mmol) was put into a three-necked flask, and 3 mL of dimethylacetamide was added. After the solid was completely dissolved, 1.8000 g (5.8062 mmol) of 4,4'-oxydiphthalic anhydride (ODPA) was weighed and put into the three-necked flask. 5 mL of dimethylacetamide was added to dissolve it. The solid content of the reaction system was controlled at 25%. After 2 h, the ice-water bath was removed. The viscosity change of the reaction solution was monitored every two hours. After stirring at room temperature for 24 h, 5.45 mL (58.0600 mmol) of 10 equivalents of acetic anhydride was added to the three-necked flask as a dehydrating agent, and 0.47 mL (5.8060 mmol) of 1 equivalent of pyridine was added as a catalyst. Stirring was continued at room temperature for 24 h before terminating the reaction. The reaction solution was poured into 150 mL of methanol to precipitate a white fibrous precipitate. The product was washed twice with water and once with methanol, filtered, and dried in a vacuum at 80°C to obtain 3.80 g of a white solid with a yield of 98%, recorded as 20% FBA / 80% TFMB / ODPA.

[0115] While the total molar amount of the diamine monomers remained constant, the ratio of the diamine monomers FBA and TFMB was varied, and the same method was used to prepare 40% FBA / 60% TFMB / ODPA, 60% FBA / 40% TFMB / ODPA, 80% FBA / 20% TFMB / ODPA, and FBA / ODPA, respectively. The synthetic routes are as follows:

[0116]

[0117] In the above formula, the ratio of m to n is the ratio of the diamine monomers FBA and TFMB.

[0118] Weigh 0.35 g of each of the five polymers prepared above and put them into a 15 mL centrifuge tube. Dissolve them completely with 4.0 mL of anhydrous dimethylacetamide, control the solid content to 8.75%, and centrifuge at 4000 r / min for 3 minutes. After the centrifugation is completed, use a dropper to absorb the supernatant and evenly coat it on a glass plate using a casting method. Place the glass plate on a constant temperature heating table, set the temperature to 80°C, and heat for 5 hours. After the temperature drops to room temperature, carefully peel off the film. The five films obtained were named PIA-6 (20% FBA / 80% TFMB / ODPA), PIA-7 (40% FBA / 60% TFMB / ODPA), PIA-8 (60% FBA / 40% TFMB / ODPA), PIA-9 (80% FBA / 20% TFMB / ODPA), and PIA-10 (FBA / ODPA). The pictures of the obtained films are shown in the figure below. Figure 9 shown.

[0119] Comparative Examples 1 to 10

[0120] Polyimide was prepared using the diamine monomer and dianhydride monomer in Table 1 in the same manner as in Example 2. The structure of the prepared polyimide is shown in Table 2.

[0121] Table 1 Types and molar ratios of monomers in Examples and Comparative Examples

[0122]

[0123]

[0124]

[0125] Table 2 Structure and film forming state of polyimide films prepared in Examples and Comparative Examples

[0126]

[0127]

[0128]

[0129] Optical performance test

[0130] The optical properties of the polyimide films prepared above were tested using a Thermo Fisher Scientific Evolution 300 UV spectrophotometer. Transmittance is a key indicator of film transparency. Polyimide film samples were cut into 1×4 cm strips, with air as a blank. The films were scanned over the entire wavelength range of 200 to 800 nm. UV-Vis software was used to analyze the transmittance of the films across the entire wavelength range. Higher transmittance indicates greater film transparency.

[0131] The optical properties of the films were tested using a CM-3600A spectrophotometer from Shanghai Konica Minolta (China) Investment Co., Ltd. The CIE Lab equation was used to characterize the optical properties, with an observer angle of 2°. The parameter YI stands for Yellowness Index, which indicates the degree of yellowing (yellowing) of colorless, transparent, translucent, or near-white polymer materials. A lower Yellowness Index indicates a closer-to-colorless and transparent film. The parameter Haze represents haze, measured using the YI (E313-73) standard. A higher haze indicates a lower gloss and transparency. The results are shown in Table 3.

[0132] Table 3 Optical properties of polyimide films prepared in Examples 2 to 11 and Comparative Examples 1 to 4

[0133]

[0134]

[0135] Thermal performance test

[0136] The thermal properties of the polyimide film were tested using a TMA450 thermomechanical analyzer manufactured by Waters, USA, to measure the film's coefficient of thermal expansion (CTE). The film samples were vacuum-dried and cut into 4×25 mm strips. The film's thickness and length were accurately measured. A nitrogen flow of 50 mL / min, a heating rate of 10°C / min, a temperature range of 40–350°C, and a preload of 0.05 N were set. After the test, the film's coefficient of thermal expansion was simulated and analyzed using TIOR software within a temperature range of 50–120°C. The film's glass transition temperature (Tg) was measured using a TMA450 thermomechanical analyzer manufactured by Waters, USA. The film samples were vacuum-dried and cut into 4×25 mm strips. The film's thickness and length were accurately measured. A nitrogen flow of 50 mL / min, a heating rate of 10°C / min, a temperature range of 40–350°C, and a preload of 0.05 N were set. After the test, the temperature-size curve of the film was simulated and analyzed using TIOR software to obtain the glass transition temperature of the film. The results are shown in Table 4.

[0137] Table 4 Thermal properties of polyimide films prepared in Examples 2 to 11 and Comparative Examples 1 to 4

[0138]

[0139]

[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A diamine monomer, characterized in that Its structure is shown in formula (I):

2. The method for preparing the diamine monomer according to claim 1, wherein The steps include: Step a: In the presence of a first catalyst and solvent a, aniline and hexafluoroacetone undergo electrophilic substitution reaction to obtain intermediate 1 represented by formula (I-a); Step b, in the presence of a second catalyst, an acid-binding agent, and solvent b, intermediate 1 undergoes an acylation reaction with p-nitrobenzoyl chloride to obtain intermediate 2 represented by formula (I-b); In step c, the intermediate 2 is subjected to a hydrogenation reduction reaction in the presence of the third catalyst and solvent c to obtain a diamine monomer represented by formula (I).

3. The method for preparing a diamine monomer according to claim 2, wherein: In step a, the first catalyst comprises one or both of p-toluenesulfonic acid and trifluoromethanesulfonic acid; and / or In step a, the solvent a is xylene; and / or In step a, the temperature of the electrophilic substitution reaction is 100° C. to 130° C., and the reaction time is 15 h to 20 h; and / or In step b, the second catalyst comprises at least one of 4-dimethylaminopyridine, pyridine or triethylamine; and / or In step b, the solvent b is tetrahydrofuran, and the acid binding agent is triethylamine; and / or In step b, the acylation reaction temperature is -5°C to 25°C, and the reaction time is 0.5h to 1h; and / or In step c, the third catalyst comprises one or both of palladium carbon or Raney nickel; and / or In step c, the solvent c is anhydrous ethanol; and / or In step c, the temperature of the hydrogenation reduction reaction is 30° C. to 60° C., the pressure is 3 MPa to 4 MPa, and the reaction time is 8 h to 10 h.

4. A polyimide compound, characterized in that Its structure is shown in formula (II): In the formula Select one of the following structures: Wherein, m and n are positive integers, and m+n=10, m=2-10.

5. The method for preparing the polyimide compound according to claim 4, wherein The steps include: The diamine monomer and the dianhydride monomer are subjected to a condensation reaction, followed by a dehydration cyclization reaction to obtain a polyimide compound represented by formula (II); Wherein, the diamine monomer is a diamine monomer represented by formula (I) or a mixed monomer of a diamine monomer represented by formula (I) and 2,2'-bis(trifluoromethyl)diaminobiphenyl; The dianhydride monomer is 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, 4,4'-oxydiphthalic anhydride or 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride.

6. The method for preparing a polyimide compound according to claim 5, wherein: The specific steps include: S1, under an inert atmosphere, dissolving a diamine monomer and a dianhydride monomer in a polar aprotic solvent, and reacting at -5°C to 25°C for 12 hours to 24 hours to obtain a polyamic acid reaction solution; S2, adding a catalyst and a dehydrating agent to the polyamic acid reaction solution, reacting at -5°C to 25°C for 12 hours to 24 hours, washing, and drying to obtain a polyimide compound represented by formula (II).

7. The method for preparing a polyimide compound according to claim 6, wherein: In step S1, the polar aprotic solvent includes at least one of N,N-dimethylacetamide, N,N-dimethylformamide or N-methylpyrrolidone; and / or In step S1, the molar ratio of the diamine monomer represented by formula (I) to 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl is (0.2-1):(0.8-0); and / or In step S1, the molar ratio of the diamine monomer to the dianhydride monomer is 1:(1-1.2); and / or In step S2, the molar ratio of the catalyst, the dehydrating agent and the diamine monomer is (1-5):(5-10):1; and / or In step S2, the catalyst is at least one of pyridine, collidine or quinoline; and / or In step S2, the dehydrating agent is acetic anhydride.

8. A low CTE colorless and transparent polyimide film, characterized in that: The invention comprises the polyimide compound according to claim 4 or the polyimide compound prepared by the preparation method according to any one of claims 5 to 7.

9. The method for preparing the low CTE colorless and transparent polyimide film according to claim 8, characterized in that: The following steps are involved: The polyimide compound is dissolved in an organic solvent, casted, the solvent is evaporated, and the film is peeled off to obtain a low CTE colorless and transparent polyimide film.

10. A flexible display device material, characterized in that: The invention comprises the low CTE colorless and transparent polyimide film according to claim 8.